Influence of oxidative stress and effect of topical application of α-tocopherol on wound healing in a diabetic animal model - Nyamadzawo, Amos T.; Nishio, Junko; Ogawa, Toshiko; Okada, Shinobu (International Journal of Research in Medical Sciences, 2022)
Background: Understanding mechanisms involved in development of diabetes mellitus-associated ulcers is vital to pioneering alternative care approaches. This study aimed to establish effects of oxidative stress (OS) and α-tocopherol’s effect on diabetic wound healing. Methods: Using two animal experimental designs surgical wounds were created in 4 groups of 9-week-old diabetic and non-diabetic rats. OS was induced through antioxidant enzyme inhibition. In experiment-1 wounds were allowed to heal. In experiment-2 varying concentrations of topical α-tocopherol and/or the ointment-base were administered to diabetic animal wounds. Intermittent comparison of wound morphology, histology and local and systemic OS parameters was done. Results: Irrespective of diabetic state, OS was associated with delayed wound size reduction and poor granulation-tissue collagen deposition. Delayed and subdued local glutathione peroxidase activity in response to wounding and OS induction was more pronounced in diabetic animals. Diabetic animals also showed higher serum malondialdehyde levels regardless of OS induction. Topical application of α-tocopherol was associated with denser wound granulation tissue collagen deposition but could not affect serum malondialdehyde levels. Conclusions: OS interferes with wound healing especially collagen deposition and the effect is more pronounced in a diabetic state. Topical α-tocopherol can improve collagen deposition in diabetic wounds but cannot counteract systemic OS, therefore combining systemic and local antioxidant supplementation has potential for use in DFU care.